“OS QUATRO QUATROS” – REFLEXÕES SOBRE UMA GINCANA DE MATEMÁTICA“THE FOUR FOURS” – REFLECTIONS ABOUT SOME ACTIVITIES ON MATHEMATICS (Revista Linhas, 2010)
Este artigo relata uma atividade desenvolvida com alunos de um curso Normal Superior durante uma gincana de matemática, que envolvia o capítulo que continha o trecho “Os quatro quatros”, do livro “O homem que calculava”, escrito por Malba Tahan. Apresentamos também algumas reflexões sobre os resultados formativos efetivos desta atividade. Palavras-Chave: Educação matemática. Formação de professores. Ensino-aprendizagem.Abstract This article is about an activity developed by students of an undergraduate teacher training course during a mathematics competition based on the chapter which contains the “The Four Fours” of the book “The Man Who Counted”, written by Malba Tahan. We present also some reflections about the effective educational results of this activity. Keywords: Mathematics education. Teacher training. Teaching-learning.